Dorsal Track Control (DTC): A Modified Surgical Technique for Atraumatic Handling of the Distal Esophagus in Esophagojejunostomy - Lehwald-Tywuschik, Nadja (J Gastric Cancer, 2019)
Surgical therapy for adenocarcinoma of the esophagogastric junction II requires distal esophagectomy, in which a transhiatal management of the lower esophagus is critical. The ‘dorsal track control’ (DTC) maneuver presented here facilitates the atraumatic handling of the distal esophagus, in preparation for a circular-stapled esophagojejunostomy. It is based on a ventral semicircular incision in the distal esophagus, with an intact dorsal wall for traction control of the esophagus. The maneuver facilitates the proper placement of the purse-string suture, up to its tying (around the anvil), thus minimizing the manipulation of the remaining esophagus. Furthermore, the dorsally-exposed inner wall surface of the ventrally-opened esophagus serves as a guiding chute that eases anvil insertion into the esophageal lumen. We performed this novel technique in 21 cases, enabling a safe anastomosis up to 10 cm proximal to the Z-line. No anastomotic insufficiency was observed. The DTC technique improves high transhiatal esophagojejunostomy.